Social innovation & the City: What is the Connection between Social Innovation and Urban Innovation ... and Why Does it Matter? - Stewart-Weeks, Martin (Institutional Knowledge at Singapore Management University, 2010)
How we build and live in cities will come to shape the discourse on sustainability and ecologically-sound thinking for the future. Martin Stewart-Weeks examines why urban innovation holds the key to this debate.